Spherical P‐modified catalysts for heterogeneous cross‐aldol condensation of formaldehyde with methyl acetate for methyl acrylate production. (11th July 2017) - Zuo, Cuncun; Li, Chunshan; Ge, Tingting; Guo, Xinpeng; Zhang, Suojiang
Abstract: A series of spherical supported catalysts were prepared for the production of methyl acrylate (MA) via cross‐aldol condensation with methyl acetate (MeOAc) and formaldehyde—the simplest aldehyde without α‐H. ZSM‐5, γ‐Al2 O3, MCM‐41, SBA‐15, and β‐zeolite were used as supports and phosphorus element (P) was selected for the active component to synthesize the catalyst to study the influence of the catalyst acid‐base properties on the yield of MA. The catalyst was characterized with X‐ray diffraction, XPS, Pyridine FTIR, BET, SEM, TEM, CO2 ‐TPD, and NH3 ‐TPD and the changes of the catalyst structure and acid properties were explored. The results showed the carbonyl polarity of methyl acetate was boosted by Lewis acid sites (L acid) and the formaldehyde activation and formation of ester enol form could be promoted by Bronsted acid sites (B acid). Using the fixed‐bed reactor, the effect of calcination temperature, catalyst loading, reaction temperature, molar ratio of reactants, and sources of phosphorus were optimized, then the catalyst life and regeneration performance were also evaluated. Lastly, the catalytic mechanism of P‐modified ZSM‐5 catalysts was proposed. Abstract : The interaction of Lewis acid and carbonyl in methyl acetate makes the carbon oxygen bond exhibit greater polarity, and the positive charge in the hydrogen atom at the α‐carbonyl position is transferred by the strong electrostatic attraction carbonyl oxygen, resulting in the formation of methyl acetate. With the interaction of B acid, the carbon of the formaldehyde is provided with a strong positive charge, which reacts with α‐carbon of enol type structure to form β‐hydroxy methyl propionate intermediate, which has a six‐membered ring structure. Under acidic conditions, a dehydration reaction takes place to form methyl acrylate. The ratio of B acid to L acid was quantified by Pyridine FTIR, and the ratio of two acids in the catalyst can be adjusted by the amount of P supported and calcination temperature. At last, a single‐pass methyl acrylate yield of 40 % was obtained by the aldol reaction of methyl acetate and formaldehyde.